1997
DOI: 10.1093/ps/76.3.482
|View full text |Cite
|
Sign up to set email alerts
|

Effect of sucrose thermal oligosaccharide caramel, dietary vitamin-mineral level, and brooding temperature on growth and intestinal bacterial populations of broiler chickens

Abstract: Two experiments were conducted to determine the effect of sucrose thermal oligosaccharide caramel (STOC) and dietary vitamin-mineral (V/M) level on growth performance and intestinal microflora of broiler chickens. In Experiment 1, Peterson x Arbor Acres male broilers (n = 384) were randomly allocated into four groups that were fed either the control diet or diets containing the antibiotic virginiamycin (11 mg/kg), 3.7% STOC or 7.5% STOC for 4 wk at brooding temperatures of 32 to 29.7 C. Weight gains for broile… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
1
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 26 publications
2
26
1
1
Order By: Relevance
“…Arribas et al (2010) recently showed that the administration of a DFA-enriched caramel obtained from fructose (containing 70% of an isomeric mixture of 13 DFAs and glycosyl-DFAs, identical to FC in this work) to colitic rats promoted a more favourable intestinal microbiota, increasing lactobacilli and bifidobacteria log 10 number of copies, as well as inducing increased concentrations of SCFA in the luminal colonic contents. Previous results on the prebiotic potential of a caramel obtained by pyrolysis of sucrose in the presence of citric acid (Manley-Harris and Richards, 1997) containing~34% of DFAs and 43% of monosaccharides indicated that DFAs and their glycosylated derivatives might represent promising candidates as prebiotic agents (Orban et al, 1997). It is important to mention here that in the present study fructose-derived caramels were used.…”
Section: Discussionmentioning
confidence: 88%
“…Arribas et al (2010) recently showed that the administration of a DFA-enriched caramel obtained from fructose (containing 70% of an isomeric mixture of 13 DFAs and glycosyl-DFAs, identical to FC in this work) to colitic rats promoted a more favourable intestinal microbiota, increasing lactobacilli and bifidobacteria log 10 number of copies, as well as inducing increased concentrations of SCFA in the luminal colonic contents. Previous results on the prebiotic potential of a caramel obtained by pyrolysis of sucrose in the presence of citric acid (Manley-Harris and Richards, 1997) containing~34% of DFAs and 43% of monosaccharides indicated that DFAs and their glycosylated derivatives might represent promising candidates as prebiotic agents (Orban et al, 1997). It is important to mention here that in the present study fructose-derived caramels were used.…”
Section: Discussionmentioning
confidence: 88%
“…When birds are reared under suboptimal experimental conditions, feed additives are more efficient (Orban et al, 1997). Growth-promoting effects of probiotic and prebiotic were more pronounced under coccidial challenge conditions rather than under unchallenged conditions (Bozkurt et al, 2014).…”
Section: Performance and Cecal Bacteria Counts Of Broilers Fed Low Prmentioning
confidence: 99%
“…population in the digestive tract of mammals are carcinogenesis inhibition [31], the decrease of blood pressure and blood cholesterol levels [32], vitamin B-complex synthesis stimulation [33] or inhibition of proliferation of undesirable bacteria such as Clostridium perfringens or Escherichia coli, among others [34,35]. Some studies have revealed that the use of DFA-containing products in animal feeding (i.e., fowls) protect against digestive tract infections [36]. These prebiotic effects are the basis of several inventions, like that described by Stoppok et al consisting of a beverage containing DFAs as dietary fiber [37].…”
Section: Ohmentioning
confidence: 99%
“…DFA V-producing enzyme has not been isolated yet and only evidences of its actions have been described [111]. Enzymatic preparation is far more developed in the case of DFA III and the non-spiroketalic DFA IV [34,36]. The abundance of reports on isolation, characterization and even gene sequencing and engineering has provided a broader pool of DFAs III and IV-producing enzymes, which might be useful tools to face the ultimate challenge: industrial enzymatic biosynthesis of DFAs.…”
Section: +mentioning
confidence: 99%